INDONESIAN’S EFFORT FACING EUROPEAN UNION ALLEGATIONS AGAINTS DUMPING PRACTIES INDONESIAN FATTY ALCOHOL PRODUCT IN 2011-2017 - Adne Dwi Kumastuti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The pupose of this research is to understand what Indonesian’s Effort Facing. European Union Allegations Against Dumping Practices Indonesian Fatty Alcohol Product in 2011 – 2017. Are Indonesia as a fatty alcohol exporting countries in the world, even EU imports of fatty alcohol from Indonesia. However, the European Union claim that Indonesia has been selling fatty alcohol to EU members at a price below their normal value. According to the result of the EU investigation, imposition of additional import duties for the fatty alcohol industry in the European Union harmed by imports of fatty alcohol from Indonesia.This research theoretically has built with Liberalism perspectives on International Relations and supported by Foreign Policy theory James N. Rosenau. Formulation of all arguments, facts, and theoretical framework on this reasearch is guided by qualitative explanation methods. Technique in this research is through by the interview and study of library. Data which is gotten and collected from the interview with Kementrian Perdagangan Republik Indonesia (KEMENDAGRI), journal books, the last thesis and then from internet has related to the problems.The research found that Indonesian’s Effort Facing European Union Allegations Againts Dumping Practices Indonesian Fatty Alcohol Product in 2011 – 2017 through suing the EU to the World Trade Organization (WTO). Indonesia suing the EU through the secretariat of the World Trade Organization (WTO) and request for consultations with the Dispute Settlement Body (DSB) of the WTO as a third party. The Government through the Ministry of Trade will be sent a letter of objection to the Eropean Union on the decision.Keywords : Eropean Union, Dumping Practices, Economic, Indonesian, Fatty Alcohol, allegations